Navigating workplace conflict in diverse academic settings: The roles of core self-evaluation and emotional intelligence in strengthening regional higher education - Rosita, Sry; Musnaini, Musnaini; Aira, Dian Mala Fithriani; Tialonawarmi, Feny (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study examines the direct effects of core self-evaluation (CSE) and emotional intelligence (EI) on workplace conflict while exploring the mediating role of perceived workplace diversity. Grounded in organizational psychology and contextualized within a regional Indonesian university, the research adopts a quantitative design, utilizing structured questionnaires administered to 94 academic staff members at Universitas Jambi. The findings indicate that neither CSE nor EI has a statistically significant direct effect on workplace conflict. However, EI is positively associated with diversity perception, which in turn significantly increases relational, task, and process conflict—demonstrating a mediated effect. In contrast, diversity does not mediate the relationship between CSE and conflict. These results reveal the complex interplay between individual psychological resources and organizational diversity in shaping interpersonal dynamics within higher education. The study highlights the importance of context-sensitive institutional strategies, including the integration of emotional intelligence training and inclusive workplace policies, in effectively managing diversity and mitigating conflict. It contributes to the broader discourse on academic workplace behavior by highlighting how personal dispositions and structural diversity jointly influence conflict outcomes, particularly within regional universities engaged in local development.